Pulmonary cavernous hemangioma: a case report - Wei Li; Xingxing Zheng; Hongzhe Tian; Yu Xi; Yuhao Liu (BMC Pulmonary Medicine)
Abstract Background Cavernous hemangiomas can occur in various internal organs like the liver, kidney, bladder, and skin, or even in subcutaneous tissues. However, they rarely occur in the lungs, making pulmonary cavernous hemangiomas (PCH) an uncommon finding. Herein, we report a rare case of pulmonary cavernous hemangioma that was surgically resected. Case presentation A 16-year-old adolescent patient was diagnosed with a pulmonary cavernous hemangioma during a physical examination. During the entry physical examination, a chest X-ray showed shadows in the upper lobe of the right lung. The patient was admitted to the Thoracic Surgery Department for further assessment. The patient had a one-year history of smoking; however, he did not experience any clinical symptoms related to respiratory diseases. Among tumor markers assessed, only the cytokeratin-19 fragment (CYFRA21-1) was elevated. Chest computed tomography (CT) showed irregular soft tissue lesions in the upper lobe of the right lung. The lesion presented as a shallow lobe with clear boundaries, accompanied by the presence of spicules around it. The lesion showed mild to moderate uniform enhancement in the arterial phase and slightly reduced in the venous phase on imaging. The lesion was anatomically close to adjacent bronchus and blood vessels. In addition, the patient had multiple enlarged lymph nodes in the mediastinum. In summary, the thoracic surgeon could not rule out the possibility of lung malignant tumors and chose to proceed with surgical excision to secure a conclusive diagnosis. Post-operative histological examination showed that the lesion consisted of dilated nodular hyperplasia rich in red blood cells, leading to a diagnosis of PCH. No recurrence has been observed since postoperative follow-up. Case presentation We reported a rare PCH case, reviewed the clinical features, imaging findings, histopathological features, and treatment options of PCH based on relevant literature, and gained a further understanding of PCH.